2017
DOI: 10.1098/rspb.2017.1636
|View full text |Cite
|
Sign up to set email alerts
|

Parsimony and maximum-likelihood phylogenetic analyses of morphology do not generally integrate uncertainty in inferring evolutionary history: a response to Brown et al.

Abstract: University of Bristol -Explore Bristol Research General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms and can be used to construct a majority-rule consensus tree that reflects this. Of the three main

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
2
14
0
1
Order By: Relevance
“…The number of such trees was highly correlated to the MP-BI topological distance (R 2 = 0.17, P < 0.01). These results corroborate most recent analyses of simulated data which reported that probabilistic methods (BI and maximum likelihood) are more accurate than MP in recovering the true phylogeny, although the precision of BI is diminished (O'Reilly et al 2016;Brown et al 2017;Puttick et al, 2017a). Interestingly, we have not found a negative association between the matrix length and the topological distance.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The number of such trees was highly correlated to the MP-BI topological distance (R 2 = 0.17, P < 0.01). These results corroborate most recent analyses of simulated data which reported that probabilistic methods (BI and maximum likelihood) are more accurate than MP in recovering the true phylogeny, although the precision of BI is diminished (O'Reilly et al 2016;Brown et al 2017;Puttick et al, 2017a). Interestingly, we have not found a negative association between the matrix length and the topological distance.…”
Section: Discussionsupporting
confidence: 92%
“…; Brown et al . ; Puttick et al ., ). Interestingly, we have not found a negative association between the matrix length and the topological distance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have advocated accuracy as the sole criterion by which to select a method [5][6][7][8][9][10][11]. Congreve & Lamsdell [9] ( problematically [2]) define the most accurate tree as the one that bears the fewest incorrect splits.…”
Section: Introductionmentioning
confidence: 99%
“…The Mk is thus a general, data-independent version of the classic Jukes-Cantor model of nucleotide evolution (Jukes & Cantor, 1969). Adoption of the Mk model in probabilistic analysis of morphology remains controversial, as doubts were cast on whether such a simple framework can accurately account for the intricacies of phenotypic evolution (Brown, Parins-Fukuchi, Stull, Vargas, & Smith, 2017;Dávalos, Velazco, Warsi, Smits, & Simmons, 2014;Puttick, O'Reilly, Oakley et al, 2017;Schrago, Aguiar, & Mello, 2018). A fundamental criticism rests on the assumption that morphological characters evolve under a common mechanism, that is, the rate of evolution at each branch is linearly correlated among characters (Goloboff, Pittman, Pol, & Xu, 2018;Tuffley & Steel, 1997); therefore, if a given character evolves faster in some lineage, it is expected that another unrelated character will also evolve relatively faster in this same lineage.…”
mentioning
confidence: 99%